POTENSI DAN EFEKTIVITAS PENGELOLAAN ZAKAT DI KABUPATEN KONAWE SELATAN - Sodiman Sodiman; P Mustafa; Muhammad Hadi; Ahmadi Ahmadi; La Hadisi (Institut Agama Islam Negeri Kendari, 2016)
Abstract Zakat is an Islamic instrument for poverty reduction and achieving the welfare of the community equally and fairly. This religious instrument has tremendous economic potential to garner a sense of social solidarity of the rich (aghniya) to the poor (fuqara), to provide aid to the poor on the basis of love, so that the poor can be free from poverty. In the context of the local area, zakat is also a great potential, including in Konsel, to eradicate poverty. But the zakat has not been able to work properly. From this research it is known that the potential zakat fitrah in Konawe Selatan high enough. The potential is there on the Muslim population that is 250 818 inhabitants (93% of the population Konawe Selatan) which annually pay zakat fitrah. The percentage of tithe payment Konsel which amounted to 99.2% claimed regular pay tithes annually. With the level of awareness of paying zakat, zakat fitrah Konawe Selatan community life 250 818 X 2.5 Kg Rice = 627 045, or if in the form of money 250 818 X Rp 20,000 = US 5.01636 billion. Zakat mal potention, viewed by the average level of public income per month, which is the level of income above US 4,600,000.00 per month of 0.8%. This figure shows the potential of tax payers mall in Konawe Selatan. While zakat agriculture, plantation, farming, trading, gold, silver and mining have not been explored in this study. The effectiveness of the management of zakat fitrah and zakat mal in Konawe Selatan yet effective. The management system is still conventional, not to use a wellorganized system; still through small groups from mosques every region, has not been done in a centralized or without a centralized management that gives direction to better and more effective. Indicators ineffectiveness are: (1) the low level of public understanding of zakat, (2) the level of public confidence in the amil zakat institutions are not yet fully developed well, as is evident by the many muzaki who pay zakat directly to mustahiq, (3) management amil zakat by not completely worked according to the principles of good management, (4) has not impacted the growing prosperity of the people who receive zakat (mustahiq), or it can be said that zakat in Konawe Selatan still categories of zakat zakat consumptive yet productive.